2013
DOI: 10.1039/c2cp43811a
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring sites to the STM tip can explain multiple peaks in single molecule conductance histograms

Abstract: Accelerated molecular dynamics and quantum conductance calculations are employed to shed light onto the electrochemical properties of the Au|1,8-octanedithiol|Au junction. Widely different contact geometries with varying degrees of roughness are examined. Strikingly, the two extreme situations considered in this work, tip-tip and tip-perfect surface junctions, give almost indistinguishable conductances. This result contrasts the usual notion that different S-Au bonding geometries combined with molecular torsio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…This suggests that the conductance histogram in simulations for elongated junctions is dominated by thermal fluctuations and is insensitive to the precise geometry of the electrodes. This result is consistent with simulations in ref that showed that the electrode shape plays a minor role in determining the conductance distribution of alkane dithiols. As shown in Figure b, the standard deviation of the conductance histogram in this case decreases with increasing Δ L for |Δ L | < 1.5 Å.…”
Section: Modeling the Conductance Histogramssupporting
confidence: 93%
See 2 more Smart Citations
“…This suggests that the conductance histogram in simulations for elongated junctions is dominated by thermal fluctuations and is insensitive to the precise geometry of the electrodes. This result is consistent with simulations in ref that showed that the electrode shape plays a minor role in determining the conductance distribution of alkane dithiols. As shown in Figure b, the standard deviation of the conductance histogram in this case decreases with increasing Δ L for |Δ L | < 1.5 Å.…”
Section: Modeling the Conductance Histogramssupporting
confidence: 93%
“…The observed gauche defects with low conductance are in agreement with the DFT-MD simulations of an alkane dithiol molecular junction in ref . However, both studies contrast with the results in refs and that suggest that when enhanced sampling is considered the formation of gauche defects for alkane dithiols becomes less favorable due to migration of the anchor group to a side of the tip. Further, we note that the bond that breaks during the pulling using the ReaxFF is the S–Au bond.…”
Section: Junction Formation and Evolutionsupporting
confidence: 87%
See 1 more Smart Citation
“…The pronounced inter est in these particular hybrid molecule-metal junctions and interfaces is due to a multitude of potential applications such as tailoring the properties of surfaces [3][4][5][6][7], chemical anchors for molecular electronics applications [8][9][10], or coating agents for the stabilization of gold nanoparticles [11,12]. Only lately, it has been realized that the consid eration of the mechanical properties of these moleculemetal hybrids becomes a crucial design factor [13][14][15][16][17][18][19][20][21][22][23][24] for nanoscale devices.…”
Section: Nanomechanics Of Bidentate Thiolate Ligands On Gold Surfacesmentioning
confidence: 99%
“…The observation of more than one conductance peak has been previously related to possible different configurations and binding geometries on the electrodes. 21,28,39,47,48 It is reasonable that when the number of molecules in the junctions is reduced, and therefore there are fewer constrains due to the interaction with other molecules, a larger number of configurations can occur. In addition, the relative rotation of the benzene rings can be blocked for closely-packed molecules, but can become more important when the molecules are dispersed.…”
Section: Conductance Histogramsmentioning
confidence: 99%